hUMSC-Exosomes suppress TREM1-p38 MAPK signaling via HMGB1-dependent mechanisms to reprogram microglial function and promote neuroprotection in ischemic stroke - Zengyu Zhang; Rong Ji; Zhuohang Liu; Zhiwen Jiang; Min Chu; Yong Wang; Jing Zhao (Journal of Nanobiotechnology)
Abstract Background Ischemic stroke induces profound neuroinflammation, where microglial activation exacerbates secondary brain injury. Human umbilical mesenchymal stem cell-derived exosomes (hUMSC-Exos) exhibit therapeutic potential, but their mechanisms in modulating microglial responses remain incompletely understood. Results Following intranasal administration, hUMSC-Exos selectively accumulated in ischemic brain regions and were internalized by microglia. In transient middle cerebral artery occlusion (tMCAO) mice, hUMSC-Exos improved neurological outcomes, reduced neuronal apoptosis, and promoted a sustained shift in microglial polarization toward an anti-inflammatory phenotype—evidenced by suppressed pro-inflammatory and elevated anti-inflammatory markers in peri-infarct areas. These effects were replicated in LPS/IFN-γ-stimulated primary microglia and BV2 cells. Microglia-specific RNA sequencing revealed that hUMSC-Exos reversed tMCAO-induced pro-inflammatory and migratory transcriptional programs, concurrently suppressing p38 MAPK while activating immunoregulatory pathways. TREM1 emerged as a critical node, with hUMSC-Exos downregulating its expression in microglia; pharmacological TREM1 inhibition (LP17) synergistically augmented the suppression of microglial activation, migration, and proliferation. Mechanistically, hUMSC-Exos attenuated NF-κB/p38 MAPK signaling, with TREM1 functioning upstream of p38 (validated by overexpression/reversal). Proteomic analysis identified HMGB1 as a key exosomal cargo—its blockade (glycyrrhizin) partially reversed hUMSC-Exos-mediated effects, restoring TREM1 expression and pro-inflammatory cytokine release, thus positioning HMGB1 upstream of TREM1. Conclusions Our findings delineate a novel HMGB1-TREM1-p38 MAPK axis through which hUMSC-Exos mitigate post-stroke neuroinflammation. By delivering HMGB1, hUMSC-Exos inhibit TREM1-dependent NF-κB/p38 activation, reprogram microglial function, and confer neuroprotection. Validated across in vivo, primary, and BV2 microglial models, and supported by multi-omics analyses, this study establishes hUMSC-Exos as a promising cell-free therapy targeting microglial reprogramming for ischemic stroke recovery. Graphical abstract